2011
DOI: 10.1016/j.snb.2010.11.044
|View full text |Cite
|
Sign up to set email alerts
|

On data analysis in PTR-TOF-MS: From raw spectra to data mining

Abstract: Recently the coupling of proton transfer reaction ionization with a time-of-flight mass analyser (PTR-TOF-MS) has been proposed to realise a volatile organic compound (VOC) detector that overcomes the limitations in terms of time and mass resolution of the previous instrument based on a quadrupole mass analysers (PTR-Quad-MS). This opens new horizons for research and allows for new applications in fields where the rapid and sensitive monitoring and quantification of volatile organic compounds (VOCs) is crucial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
126
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 154 publications
(137 citation statements)
references
References 30 publications
2
126
0
1
Order By: Relevance
“…Calibration was performed by dynamically diluting the VOC standards to ppbv levels using purified ambient air. Details about the data evaluation can be found in Müller et al (2010), Kaser et al (2013), and Cappellin et al (2011).…”
Section: Instrumentationmentioning
confidence: 99%
“…Calibration was performed by dynamically diluting the VOC standards to ppbv levels using purified ambient air. Details about the data evaluation can be found in Müller et al (2010), Kaser et al (2013), and Cappellin et al (2011).…”
Section: Instrumentationmentioning
confidence: 99%
“…S1 in Supplementary material). Dead time correction and peak extraction were performed according to a procedure described elsewhere using a modified Gaussian peak shape (Cappellin et al 2011). Subsequently, the peaks associated with the PTR-MS ion source including m/z = 32 (O2 + ) and m/z = 37 (water cluster ion) were eliminated.…”
Section: Ptr-tof-ms Data Analysismentioning
confidence: 99%
“…This technique uses H 3 O + reagent ions and can have time resolution of 1 Hz or better. The recent development of PTR-MS instruments that use high-resolution time-of-flight mass spectrometers (PTR-ToF-MSs) has greatly expanded the number of measurable species, enhanced the technique's suitability to mobile platforms, and improved our ability to speciate specific ion masses (Jordan et al, 2009;Graus et al, 2010;Cappellin et al, 2011;Yuan et al, 2016a). For example, the resulting complex PTR-ToF-MS mass spectra in forested environments (Kim et al, 2010) and biomass burning (Brilli et al, 2014;Stockwell et al, 2015) have been reported.…”
mentioning
confidence: 99%